Evaluasi Penyusunan Laporan Penyelenggaraan Pemerintahan Daerah Di Bagian Tata Pemerintahan Sekretariat Daerah Kota Palembang - Austin, Trecy; Chola, Siti (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
.This research was carried out in the Governance Section of the Regional Secretariat of Palembang City, this aims to determine the Evaluation of the Preparation of Regional Government Implementation Reports for Palembang City, South Sumatra Province. For the population and sample, the researchers took several officials and staff in the Governance Department as well as 3 (three) departments, namely the Trade Department, the Employment Service, and the Palembang City Education Service, totaling 8 respondents. The theory used to evaluate the CIPP evaluation model is by Daniel L. Stufflebeam. This research uses a descriptive method with a qualitative approach. The data used in this research are primary data and secondary data, data taken by distributing questionnaires to all 8 respondents by means of interviews. Qualitative data will be described using words or sentences separated according to categories to obtain conclusions. The research results show that in context evaluation, the preparation of the Palembang City LPPD is mandated by Law Number 23 of 2014 and is technically still regulated in PP Number 13 2019 regarding LPPD to the Government. Physical support in preparing the LPPD is contained in the guidelines for preparing the LPPD issued by the Ministry of Home Affairs and includes technical guidance, facilitation and consultation activities.